2010
DOI: 10.1007/s00296-010-1423-4
|View full text |Cite
|
Sign up to set email alerts
|

Association of cytosine–adenine repeat polymorphism of the estrogen receptor-β gene with rheumatoid arthritis symptoms

Abstract: The influence of the polymorphism of the estrogen receptor-beta gene, cytosine-adenine (CA) dinucleotide repeat in intron 6, in the occurrence of rheumatoid arthritis (RA) was investigated. Forty-seven RA patients and 36 control subjects with osteoarthritis (OA) were recruited. CA repeat polymorphism was examined using denaturing high-performance liquid chromatography (WAVE DNA Fragment Analysis System). The mean number of CA repeats was significantly higher in RA than in OA patients. Two groups were establish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 19 publications
1
6
0
Order By: Relevance
“…In the present study, we ana-lyzed the CA repeat polymorphism by direct sequencing, a method typically used for the analysis of microsatellite polymorphisms. The mean CA repeat length observed for the RA patients was the same as that reported in a previous study [13]. Thus, neither the patient background nor the methods used for the analyses in the present study are likely to have resulted in the lack of association observed here.…”
Section: Discussionsupporting
confidence: 83%
See 4 more Smart Citations
“…In the present study, we ana-lyzed the CA repeat polymorphism by direct sequencing, a method typically used for the analysis of microsatellite polymorphisms. The mean CA repeat length observed for the RA patients was the same as that reported in a previous study [13]. Thus, neither the patient background nor the methods used for the analyses in the present study are likely to have resulted in the lack of association observed here.…”
Section: Discussionsupporting
confidence: 83%
“…We investigated the association of the CA repeat polymorphism in the intron 6 of the ERβ gene with RA and OA to follow up on the findings from a previous report [13]; however, our results did not reveal significant differences between RA and OA patients with respect to allele and genotype frequencies identified at this locus. Based on the patient characteristics ( Table 1), we evaluated the degree of severity of RA in the patients according to Ochi et al [15].…”
Section: Discussionmentioning
confidence: 77%
See 3 more Smart Citations